Cybersecurity Incident Response How to Contain, Eradicate, and Recover from Incidents - Thompson, Eric C. (Apress, 2018)
Create, maintain, and manage a continual cybersecurity incident response program using the practical steps presented in this book. Don't allow your cybersecurity incident responses (IR) to fall short of the mark due to lack of planning, preparation, leadership, and management support. Surviving an incident, or a breach, requires the best response possible. This book provides practical guidance for the containment, eradication, and recovery from cybersecurity events and incidents. The book takes the approach that incident response should be a continual program. Leaders must understand the organizational environment, the strengths and weaknesses of the program and team, and how to strategically respond. Successful behaviors and actions required for each phase of incident response are explored in the book. Straight from NIST 800-61, these actions include: Planning and practicing Detection Containment Eradication Post-incident actions What You'll Learn: Know the sub-categories of the NIST Cybersecurity Framework Understand the components of incident response Go beyond the incident response plan Turn the plan into a program that needs vision, leadership, and culture to make it successful Be effective in your role on the incident response team.